Optimization of 18F Radioisotope Production with Cyclone 18/9 MeV IBA Cyclotron Installed at NINMAS - Rabbani, AFM Masum; Mia, Md Shohag; Mehdi, Hasan; Biswasarma, Sanchoy Chandra; Islam, Md Ariful; Uddin, Md Jashim; Biman, Tanvir Ahmed; Ul Azim, Mohammad Anwar; Hossain, Md Nahid (Dhaka University Journal of Science, 2023)
A cyclotron is a particle accelerator, which employs electromagnetic fields to accelerate charged particles to extremely high speeds and energy. It is used to create radioisotopes for radiopharmaceuticals, which are used to diagnose and treat cancer. Because cyclotron-produced radiopharmaceuticals are exceptionally effective in identifying various cancers. Cyclotrons are fast evolving and will play an increasingly important role in the healthcare industry, particularly in advanced medical imaging techniques like positron emission tomography-computed tomography (PET-CT) and single photon emission computed tomography (SPECT). An 18/9 MeV cyclotron (18 MeV for proton and 9 MeV for deuteron, Model: Cyclone 18/9, IBA) was installed at the National Institute of Nuclear Medicine and Allied Science (NINMAS), Bangladesh Atomic Energy Commission (BAEC). Radioisotopes such as 18F, 11C, 13N, and 15O can be produced with this cyclotron. Solid target option is also available here which can be used for producing 67Ga, 68Ga, 124I, 123I, 111In, 99mTc, 64Cu, and 89Zr radioisotopes. 18F is the radioisotope of choice for many radiopharmaceuticals due to its glucose analogous and half-life of 110 min. We are producing FDG on a regular basis. For a 60-minute bombardment time, a 40 to 50 micro amp beam current is employed to produce 18F with a mass of 2500 to 3500 mCi. Because of the variable production parameters used, the production of 18F varies. Parameters used in the production of 18F radioisotope are limited to physical factors such as target material, target volume, collimator, stripper foil, and ion source. As a result, we consider 18F yield to be the most important aspect in providing sufficient activity since we want to find the best operating point that minimizes both production time and cost. In order to produce an optimal 18F radioisotope production, all parameters such as dee voltage, vacuum label, beam current, irradiation time, amount of enriched 18O water, target pressure, and others are taken into account. Dhaka Univ. J. Sci. 71(1): 56-59, 2023 (Jan)